Assessment of climate change impact on hydrological components of Ponnaiyar river basin, Tamil Nadu using CMIP6 models. Issue 3 (15th February 2023) - Balu, Abinaya; Ramasamy, Saravanan; Sankar, Guganesh
Abstract: This study aims to assess the climate change impacts on the hydrological components in the Ponnaiyar river basin using the Soil Water Assessment Tool (SWAT) model. This study used 13 Global Climate Models (GCM) from Coupled Model Inter-comparison Project Phase 6 (CMIP6). Based on the performance evaluation of 13 CMIP6-GCMs, the best GCMs selected for future projections were EC-Earth3, MPI-ESM1-2-LR and MPI-ESM1-2-HR. SWAT-CUP (SWAT – Calibration and Uncertainty Programs) successfully calibrated and validated the SWAT model. The SWAT model simulated the hydrological components of the basin for the future period under SSP245 and SSP585 emission scenarios. The results indicated increased streamflow over the projected period due to increased rainfall in the basin. The annual surface runoff varied from −20.41 to −15.46%, −10.51 to 18.34% and 73.88 to 134.56% under the SSP585 scenario for the 2020s, 2050s and 2080s, respectively. For the future 2020s, the water yield varied from −7.02 to 11.36% and −1.41 to 6.15% for SSP245 and SSP585. During the 2050s and 2080s, there was an increase in water yield (7.89–21.18% and 36.12–115.25%) under SSP245 and SSP585 future climate scenarios. This study could help policymakers and stakeholders to develop adaptive strategies for the Ponniyar river basin. HIGHLIGHTS: This study used a bias-corrected CMIP6 dataset for climate change projections. Best GCMs were selected based on the performance evaluation of GCMs for the Ponnaiyar river basin. The SWAT model performed well in both gauging stations in the basin. The results indicated increased streamflow over the projected period. Graphical Abstract